Cultural identification of a person in the works of William Kurelek - Beregovska, Khrystyna O.; Tarasenko, Olga A.; Nahorniak, Khrystyna M.; Pavlyshyn, Anastasiia D.; Davydova, Karina D. (Linguistics and Culture Review, 2021)
Ethnic groups in Canada try not to dissolve in a foreign national environment and to preserve their identity. Polish-Ukrainian relations are an important topic in the context of studying the immigrant Canadian environment. William Kurelek was interested in this issue and managed to prove the role of Ukrainians in shaping a multicultural Canadian society. The authors of this study aimed to characterize the preconditions and history of the thematic series of Ukrainian immigrants and The Polish Canadians on the basis of artistic works. The works of William Kurelek were characterized and special attention was paid to Polish-Ukrainian motives in his work. The models of Ukrainian-Polish relations through the author's prism of understanding and observing the traditions and culture were derived. Issues of religious tradition, prairie duties, folk celebrations, upbringing, ethnic life and friendship were raised. In his paintings, William Kurelek raised these issues.